2007
DOI: 10.1128/mcb.00030-07
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair and Transcriptional Deficiencies Caused by Mutations in the Drosophila p52 Subunit of TFIIH Generate Developmental Defects and Chromosome Fragility

Abstract: The transcription and DNA repair factor TFIIH is composed of 10 subunits. Mutations in the XPB, XPD, and p8 subunits are genetically linked to human diseases, including cancer. However, no reports of mutations in other TFIIH subunits have been reported in higher eukaryotes. Here, we analyze at genetic, molecular, and biochemical levels the Drosophila melanogaster p52 (DMP52) subunit of TFIIH. We found that DMP52 is encoded by the gene marionette in Drosophila and that a defective DMP52 produces UV light-sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 51 publications
6
75
0
Order By: Relevance
“…Thus, to direct the expression of Dmp52i, we first used the MS1096 driver, which directs the expression of Gal4 in the dorsal domain of the wing pouch; we then crossed these flies with flies carrying dsRNA against Dmp52 (Dmp52i) from the Vienna Resource Center. Consistent with results from our previous work using Dmp52 mutant alleles (Fregoso et al, 2007), we observed a reduction in the size of adult wings in flies expressing Dmp52i compared with flies carrying only the driver (Fig. 3).…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, to direct the expression of Dmp52i, we first used the MS1096 driver, which directs the expression of Gal4 in the dorsal domain of the wing pouch; we then crossed these flies with flies carrying dsRNA against Dmp52 (Dmp52i) from the Vienna Resource Center. Consistent with results from our previous work using Dmp52 mutant alleles (Fregoso et al, 2007), we observed a reduction in the size of adult wings in flies expressing Dmp52i compared with flies carrying only the driver (Fig. 3).…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihsupporting
confidence: 92%
“…In a previous analysis of mutant alleles in Dmp52, we discovered the presence of chromosomal aberrations in neuroblast metaphasic chromosomes (Fregoso et al, 2007). This defect may be related to the increase in apoptosis observed in the wing discs that have reduced levels of Dmp52.…”
Section: Dp53 Physically Interacts With the Dmp52 Subunit Of Tfiihmentioning
confidence: 89%
See 2 more Smart Citations
“…Along this line, phosphorylation of Ser751 in XPB needs to be carefully regulated to permit the incision during NER (34). XPB retention and ATPase stimulation for appropriate NER and transcription are dependent on the integrity of Ydj1-binding motif present in Tfb2/p52 to avoid strong defects in Drosophila (35). The other two motives present in Tfb2/p52, located in the C-terminal part, contain key residues to establish contact with Tfb5 (36) (Fig.…”
Section: Ner Efficiency Is Reduced In Ydj1δmentioning
confidence: 99%